2016
DOI: 10.4103/2231-0762.175405
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Streptococcus mutans property of a chitosan: Containing resin sealant

Abstract: Objective:This study sought to assess the inhibitory effect of chitosan-containing sealants against Streptococcus mutans.Materials and Methods:The antibacterial activity of the resin sealant was evaluated by direct contact test following the addition of 0, 1, 2, 3, 4, and 5 wt% chitosan. At 3, 6, 9, 24 and 48 h, 1 and 3 months, 10 μl of the microbial suspension in contact with resin sealant was cultured to count the number of colonies. Data were analyzed by one-way one-way analysis of variance (ANOVA), repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Studies that used CFU counting to assess the antibacterial effects found a significant reduction in CFU counts with 5% ZnM [ 10 ], 2.5 and 5% SnM [ 10 ], 2.5 and 5% METAC [ 11 ], 5% DMAHDM [ 21 , 27 ], 2% TAT [ 12 ], 0.5 and 1% ZnO [ 28 ], 0.5 and 1% CaF 2 [ 28 ], 4% MAE-DB [ 30 ], 2, 2.5, 3, 4 and 5% chitosan [ 31 , 34 ], 0.25, 0.5 and 1% Se [ 13 ], Teethmate F-1 [ 34 ], Seal & Protect [ 34 ] and 1% DMAE-CB [ 35 ] sealants in comparison to the controls or other tested groups ( Table 4 ). There was a wide variation in the data reported among the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that used CFU counting to assess the antibacterial effects found a significant reduction in CFU counts with 5% ZnM [ 10 ], 2.5 and 5% SnM [ 10 ], 2.5 and 5% METAC [ 11 ], 5% DMAHDM [ 21 , 27 ], 2% TAT [ 12 ], 0.5 and 1% ZnO [ 28 ], 0.5 and 1% CaF 2 [ 28 ], 4% MAE-DB [ 30 ], 2, 2.5, 3, 4 and 5% chitosan [ 31 , 34 ], 0.25, 0.5 and 1% Se [ 13 ], Teethmate F-1 [ 34 ], Seal & Protect [ 34 ] and 1% DMAE-CB [ 35 ] sealants in comparison to the controls or other tested groups ( Table 4 ). There was a wide variation in the data reported among the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial activity of chitosan could be attributed to its cationic nature. Cationic materials are able to degrade the cell wall structure and cell membrane of bacteria, which in turn leads to the exposure of the cell membrane to osmotic shock and exudation of the cytoplasmic content, eventually followed by cell death [29]. In a study in this regard, Costa et al [30] observed that chitosan was largely effective against the adherence and biofilm formation of S. mutans, and its action was evident in the inhibition of the initial adherence and biofilm formation and disruption of the mature biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan is a cationic material, as it contains one primary amine group. This polysaccharide can adhere to the bacterial cell wall and degrade its structure, as well as the cell membrane of bacteria [ 19 , 20 ]. Nanosized chitosan also exhibits superior antimicrobial activities [ 20 ].…”
Section: Introductionmentioning
confidence: 99%